KEMAMPUAN BERPIKIR REFLEKTIF FISIKA PESERTA DIDIK SMA SE-KOTA MAKASSAR - Alivka, Grivthy; Martawijaya, Muhammad Agus; Hasyim, Mutahharah (Program Studi Pendidikan Fisika Jurusan Fisika Fakultas Matematika, Ilmu Pengetahuan Alam, dan Kebumian (FMIPAK), Universitas Negeri Manado, 2024)
This research aims to determine the physics reflective thinking abilities of high school students in Makassar City. Reflective thinking is one of the characteristics of formal operational thinking. The sample was class XII students from each of the four schools, namely SMA Negeri 6 Makassar, SMA Negeri 8 Makassar, SMA Negeri 9 Makassar, dan SMA Negeri 18 Makassar totalling 159 students. The research data was obtained by giving a 10-item essay test. The analysis technique used is quantitative descriptive analysis. The research results show that the average obtained by high school students in Makassar City is 9,61 and is in the low category. Based on the results of the analysis and interviews that have been conducted, the low ability of students' reflective thinking cannot be separated from various factors that influence it, such as students still solving problems directly, students considering physics to be a difficult subject and memorizing a lot of formulas so that students are less interested in learning physics, and Students still make mistakes in answering questions when given the opportunity to correct their answers.